First of we have the equation,
6x + 4x - 6 = 24 + 9x
Grouping all the x's onto one side we get,
6x + 4x - 9x = 24 + 6
10x -9x = 30
x = 30
Checking our answer we get,
6(30) + 4(30) - 6 = 24 + 9(30)
180 + 120 - 6 = 24 + 270
300 - 6 = 294
294 =294 this means our answer is correct.
Hope this was helpful
The average of x + 6,6x + 2, and 2x is 4x-7. What is x?
In order to find the average of the numbers you have to add all of them and then divide by the amount of numbers you have to average.
[(x + 6) + (6x+2) + 2x ]/3 = 4x-7
Getting rid of the denominator, by multiplying by 3 on both sides,
[(x + 6) + (6x+2) + 2x ] = 12x - 21
Grouping all the x's
[(x + 6x + 2x) + 8] = 12x - 21
[9x+8] = 12x -21
-3x = -29
x = 29/3
Hope I didin't make any silly mistakes lol.
First we can start off by plugginng in the f(17)
In the function when you plug in a value greater than or equal to 7 you use the formula x + 13,
so your next function is f(f(30)),
you can do the same thing becasue 30 is greater than 7,
so your new function is f(43),
Then you can do this one last time becasue 33 is greater than 7,
and you are left with 56.
f(f(f(17))) = 56
We have the question The equation 2x - 3/(x - 2) = 4- 3/(x - 2) has how many roots?,
first we can simplify the equation.,
2x-3/x-2 = 4x-11/x-2
if we cross multiply we get a quadratic equal to a quadratic..
We can't have a degree higher than 2...
therefore there are 2 roots to the equation
p.s correct me if im wrong.